PEMBUATAN KONTEN EDUKASI DIGITAL UNTUK MENINGKATKAN KESADARAN WAJIB PAJAK DAERAH DI PROVINSI KALIMANTAN TENGAH MELALUI PROGRAM MBKM DI BADAN PENDAPATAN DAERAH - Sametanu Julian; Samuel Hova Raditia; Vivy Kristinae (Jurnal Pengabdian Masyarakat Berkelanjutan, 2026)
The low awareness of regional taxpayers is a crucial challenge for the optimization of Regional Original Revenue (PAD) in Central Kalimantan Province. The Independent Learning Independent Campus Program (MBKM) offers strategic solutions through the involvement of students in the creation of digital educational content at the Regional Revenue Agency (Bapenda). This service activity aims to increase public tax literacy through the production of educational short videos based on the CapCut application. The implementation method uses a service learning approach with three stages: planning, implementation, and evaluation. The results of the activity showed that MBKM students succeeded in producing 24 regional tax education video content which were distributed through Bapenda's social media platform. The content produced obtained a significant level of engagement with dynamic visual characteristics, concise narratives, and problem-solution structures that are relevant to millennial and Gen Z audiences. This program proves that the integration of MBKM with local government agencies is effective as a digital-based public communication strategy to increase taxpayer awareness while developing students' professional competencies.